2008
DOI: 10.1007/s10681-008-9831-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of coincident QTL for days to heading, spike length and spikelets per spike in Lolium perenne L.

Abstract: Byrne, S., Guiney, E., Barth, S., Donnison, I. S., Mur, L. A. J., Milbourne, D. (2009). Identification of coincident QTL for days to heading, spike length and spikelets per spike in Lolium perenne L. Euphytica, 166, (1), 61-70. S. Byrne was awarded a Teagasc Walsh Fellowship/Ireland to undertake this study IMPF: 01.40 Sponsorship: BBSRC RONO: BBS/E/W/00003134BFlowering time is a trait which has a major influence on the quality of forage. In addition, flowering and subsequent seed yields are important traits fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…Moreover, this trait was highly heritable as it was reported previously by Byrne et al (2009). Although the number of spikelets and florets per effect on plant phenotypic performance.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Moreover, this trait was highly heritable as it was reported previously by Byrne et al (2009). Although the number of spikelets and florets per effect on plant phenotypic performance.…”
Section: Discussionsupporting
confidence: 51%
“…High heritabilities were observed for the studied seed yield traits (Table 1), even though previous study of Casler et al (1996) stated that the seed yield appears to be a moderately heritable trait. The panicle length, known to be governed by genetic factors with minimal environmental influence, has shown highest heritability, thus selection for this trait would be effective in future breeding programs as it is likely to be controlled by additive genes (Byrne et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the latter experiment, plant height was measured at harvest when the plants were headed while measurements were made during the vegetative phase in the other studies. Furthermore, on several studies, QTL of heading date were found in the same region of LG7 (Armstead et al 2004Studer et al 2008b;Barre et al 2009;Byrne et al 2009). In our study, QTL of heading date were also located in this region (data not shown).…”
Section: Plant Growth Traitsmentioning
confidence: 96%
“…Up to now, all QTL studies on perennial ryegrass only involved biparental populations. Their parents could be chosen with opposite phenotypes for the trait of interest as for crown rust resistance in the F1 populations (Dumsday et al 2003;Muylle et al 2005a, b;Pfender et al 2011), for flowering time with the F1 population studied by Byrne et al (2009), for leaf length (F1 population, Barre et al 2009), for biomass in the F2 population in the study of Anhalt et al (2008) or for sugar content (Jones et al 2002b). The parents could also be chosen for their diverse origin: geographical as in the F1 population studied by Faville et al (2004) or in the F2 population described by Jensen et al (2005a), or genetic as in the population p150/112 coming from the cross between a hybrid F1 and a doubled-haploid plant (Jones et al 2002a).…”
Section: Rust Tolerancementioning
confidence: 99%
“…This is in agreement with a more recent study of Yamada et al (2004), who found a positive correlation between plant height, tiller size, spike length, and the number of spikelets per spike. These morphological traits have been shown to be highly heritable (Elgersma 1990;Yamada 2004;Byrne 2009). Although the number of spikelets and florets per inflorescence may vary to some extent from season to season, between species and cultivars, this component is not found to have a large effect on seed yield in perennial ryegrass (Hampton and Hebblethwaite 1983;Elgersma 1990).…”
Section: Spikelets and Florets Per Inflorescencementioning
confidence: 99%